Проблемы человека в информационную эпоху - Кадиграбов, Д.; Башлак, А. (ХНУРЭ, 2012)
The mankind inevitably enters an information epoch. Weight ofinformation economy constantly increases, and its share expressed in total working hours, for economically developed countries already today makes 40- 60 % and it is expected that to the end of the century it will increase for 10- 15 %. One of criteria of transition of a society to postindustrial and further to the information stage of development.